A rare case of a patient with hypethyroidism after hypothyroidism - Todorova, Biljana; Bitoska, Iskra; Mucha, Argjent; O. Georgieva Janev; Milenkovikj, Tatjana (Georgian Business Press LLC, 2023)
Primary hypothyroidism caused by an underlying autoimmune thyroiditis disease is very common in clinical practice, while one of the most commonly seen types of hyperthyroidism states is Graves’ disease. In hypothyroidism, patients are thought to be lifelong treated with substitution therapy with the lacking levothyroxine hormone. Usually due to the started autoimmune process that progressively destroys the thyroid tissue, the doses of levothyroxine increase in a different period of time during the follow ups. Rarely, the doses need to be tapered down, and that is the exact moment when the physician should be suspicious of a possible conversion from a hypothyroid state to a hyperthyroid one. We describe a case of a woman who was diagnosed with hypothyroidism and treated with suitable doses of levothyroxine, and then gradually the levothyroxine doses were tapered and eventually discontinued because of the clinical and laboratory confirmed state of hyperthyroidism- requiring a treatment with thiamazole. To our knowledge, this case is one of rarest worldwide so far published cases that illustrate the shortest time interval between the diagnosis of hypothyroidism and its switch to a hyperthyroid state.
Keywords: hyperthyroidism; hypothyroidism